A study of multiorgan dysfunction in asphyxiated neonates - S. Singh, Khangembam; Sengar, G. S. (International Journal of Contemporary Pediatrics, 2016)
Background: Perinatal asphyxia is an important cause of neonatal mortality, morbidity and late sequeale in developing countries like India. Each year 4 million neonates die worldwide, representing 38 % of all deaths of children less than 5 years of age. It is a study of the clinical profile, the frequency and pattern of organ involvement and the impact of different organ system involvement on early neonatal morbidity and mortality in asphyxiated neonates. Methods: The study was conducted in Level-III NICU of Department of Pediatrics, S P Medical College, Bikaner. 190 asphyxiated neonates were studied after due approval from Ethics committee and parental consent. The clinical and Biochemical parameters were analyzed and classified each of the organ system dysfunction as per the criteria defined. Multiple organ dysfunction is defined as involvement of two or more than two organ system. Results: Multiple organ dysfunction occurred in 63.1% infants and 27.6% died during the study; Central Nervous System (CNS) was most frequently involved (69.4%). Severe CNS injury (42 infants i.e. 22.1%) always occurred with involvement of other organs, although moderate CNS involvement was isolated in 90 infants. Renal involvement occurred in 52.1%, pulmonary in 44.2%, cardiac in 48.4% infants. Respiratory involvement having 53.3% of mortality had maximum of all other organ system involvement. Involvement of Two organ system occurred in 39 infants as compared to three and four organ system involvement in 44 and 37 infants respectively. Four organ system involvements accounted 72.9% mortality whereas two and three organ system involvement contributed 20.5% and 38.6% respectively. Three and Four organ system involvement had significant statistical association to mortality; p value <0.05 and <0.0001 respectively. Conclusions: Multiorgan Dysfunction (MOD) remains an essential entity of perinatal asphyxia. The result further delineates the clinical spectrum of Multi organ dysfunction and emphasizes the need of global management in asphyxiated new born babies.